2021
DOI: 10.1111/gbb.12772
|View full text |Cite
|
Sign up to set email alerts
|

From fruitless to sex: On the generation and diversification of an innate behavior

Abstract: Male sexual behavior in Drosophila melanogaster, largely controlled by the fruitless (fru) gene encoding the male specific FruM protein, is among the best studied animal behaviors. Although substantial studies suggest that FruM specifies a neuronal circuitry governing all aspects of male sexual behaviors, recent findings show that FruM is not absolutely necessary for such behaviors. We propose that another regulatory gene doublesex encoding the male‐specific DsxM protein builds a core neuronal circuitry that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…dsx is expressed in the central nervous system (CNS) of larvae, pupae, and adults (Lee et al, 2002 ). DSX F is expressed in ~700 neurons; while DSX M is expressed in about 900 neurons, the majority of which also express FRU M (Peng et al, 2021 ). The ventral nerve cord contains around two-thirds of all dsx -expressing neurons in the CNS, most of them found in the abdominal ganglion (Pan and Baker, 2014 ).…”
Section: Doublesex In Sexually Dimorphic Nervous System and ...mentioning
confidence: 99%
“…dsx is expressed in the central nervous system (CNS) of larvae, pupae, and adults (Lee et al, 2002 ). DSX F is expressed in ~700 neurons; while DSX M is expressed in about 900 neurons, the majority of which also express FRU M (Peng et al, 2021 ). The ventral nerve cord contains around two-thirds of all dsx -expressing neurons in the CNS, most of them found in the abdominal ganglion (Pan and Baker, 2014 ).…”
Section: Doublesex In Sexually Dimorphic Nervous System and ...mentioning
confidence: 99%
“…Previous studies have shown that the neural circuits underlying sexual and aggressive behaviors are highly intertwined and regulated at least partially by Fru M in male flies. In addition to specifying the neural circuitry controlling most aspects of male sexual behaviors [ 30 , 31 , 33 , 86 , 87 ], Fru M is also involved in controlling the sexually dimorphic intensity and pattern of fighting in the two sexes [ 88 , 89 ]. A subset of octopamine (OA) neurons in the subesophageal ganglion (SOG) that regulate behavioral choice between courting and fighting co-express Fru M [ 90 , 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual behavior in Drosophila melanogaster is an excellent model in which to investigate the neuronal basis underlying social behavior because they are innate and robust [1][2][3]. Wild-type male and female flies can achieve copulation without social learning experiences during adulthood [4,5]. Drosophila sexual behaviors include stereotypic male courtship rituals such as orienting to a female, extending an ipsilateral wing to produce courtship songs, tapping and licking the female, attempting copulation, and finally copulation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Sex-specific dsx transcripts are translated in both sexes to produce the sex-specific proteins Dsx M or Dsx F , which control male and female differentiation, respectively [15,[41][42][43]. In contrast, fru proteins (Fru M ) control male courtship and are male-specific [1,5,44,45]. Although Fru M proteins are not produced in females, neurons expressing the fru transcript (fru + ) are crucial for female sexual receptivity, as silencing these fru + neurons impairs female receptivity [44,46].…”
Section: Introductionmentioning
confidence: 99%